Seismic isolation design for simply-supported beam bridges based on the energy balance method under near-fault ground motions. Issue 145 (June 2021) - Li, Yu; Li, Chen; Zhao, Guo-Hui
Abstract: The seismically isolated simply-supported beam bridge (SISBB) with the seismic isolation bearing (SIB) is converted into an equivalent bilinear single-degree-of-freedom system. Then, by inputting the 139 near-fault ground motion (GM) records into the equivalent system, the parametric study on the near-fault seismic input energy spectra ( S EI ) of the SISBB is conducted by considering the equivalent system parameters and the near-fault GM characteristics. So, it can be found that: the increase of post-yield stiffness ratio ( η e ) can slightly increase the peak values of the near-fault S EI, and η e = 0.2 can be used to calculate the near-fault S EI design spectra of the SISBB; with the increase of the damping ratio ( ξ e ) (or ductility ratio ( μ e )), the spectral values of the near-fault S EI increases, the hysteretic energy dissipation capacity of the SIB decreases, and the damping energy dissipation capacity of the equivalent system increases; when μ e ≥ 10, the effect of μ e on the near-fault S EI can be ignored; the softer the site soil or the smaller the Joyner-Boore distance to rupture plane ( R jb ) is, the greater the near-fault S EI is; if the near-fault S EI with a standard peak ground acceleration (PGA) is known, the near-fault S EI with other PGAs can be obtained by multiplying the (PGAOther /PGAStandard ) 2 by the spectral values of the near-fault S EI with a standard PGA. Finally, the near-fault S EI design spectra of the SISBB are obtained, and the seismic isolation design for SISBB based on the energy balance method is proposed, the feasibility of which is verified by a case study. Highlights: The seismically isolated simply supported beam bridge (SISBB) with the seismic isolation bearing (SIB) is converted into the equivalent bilinear single-degree-of-freedom system. Then, by inputting the 139 near-fault ground motion (GM) records into the equivalent system, the parametric study on the near-fault seismic input energy spectra ( S EI ) of the SISBB is conducted by considering the influence of the equivalent system parameters (period ( T e ), post-yield stiffness ratio ( η e ), damping ratio ( ξ e ), and displacement ductility ratio ( μ e )) and the near-fault GM characteristics (site classification, Joyner-Boore distance to rupture plane ( R jb ), and peak ground acceleration (PGA)). The near-fault S EI design spectra of the SISBB are obtained. Under the near-fault GMs, the seismic isolation design for simply supported beam bridges based on the energy balance method is proposed.